Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1242/jcs.187971
|View full text |Cite
|
Sign up to set email alerts
|

Proplatelet formation is selectively inhibited by collagen type I through Syk-independent GPVI signaling

Abstract: Collagen receptors GPVI (also known as GP6) and integrin α2β1 are highly expressed on blood platelets and megakaryocytes, their immediate precursors. After vessel injury, subendothelial collagen becomes exposed and induces platelet activation to prevent blood loss. Collagen types I and IV are thought to have opposite effects on platelet biogenesis, directing proplatelet formation (PPF) towards the blood vessels to prevent premature release within the marrow cavity. We used megakaryocytes lacking collagen recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 49 publications
(62 reference statements)
6
52
0
Order By: Relevance
“…To this end, we confirmed that the bone-like structures at the outer linings of femur or sternum sections are positive for collagen I 21 (Supplementary Fig. 3A), and partly positive for osteocalcin (Supplementary Fig.…”
Section: Resultssupporting
confidence: 60%
“…To this end, we confirmed that the bone-like structures at the outer linings of femur or sternum sections are positive for collagen I 21 (Supplementary Fig. 3A), and partly positive for osteocalcin (Supplementary Fig.…”
Section: Resultssupporting
confidence: 60%
“…Femurs of mice aged 6–12 weeks were sectioned and stained as described previously (Kawamoto, 2003; Semeniak et al, 2016). In brief, megakaryocytes were stained with anti-GPIX antibody (emfret analytics, Eibelstadt, Germany), CD105 (eBioscicnce) was used as an endothelial cell marker.…”
Section: Methodsmentioning
confidence: 99%
“…MKs express two main receptors for collagen, integrin-α2β1 and glycoprotein VI [47]; however, MK expression of leukocyte-associated immunoglobulin-like 1 (LAIR1) and discoidin domain receptor (DDR1) that also bind collagen have been described in the literature [48,49]. Early MK progenitors (CFU-MK) have a lower affinity for adhering to collagen compared to later MK progenitors [50], which is interesting as integrin-α2β1 and glycoprotein VI expression occurs early in MK development [50,51]. It has been established that collagen I inhibits proplatelet formation (PPF) in order to prevent the release of immature platelets in the bone marrow, while collagen IV and laminin support PPF in the sinusoids [52].…”
Section: Integrins As Ecm Sensors In the Context Of Megakaryocytosismentioning
confidence: 99%